Implementasi Pendidikan Nilai Dalam Pendidikan Agama Islam - Imelda, Ade (Universitas Islam Negeri Raden Intan Lampung, 2017)
Values education is at the core of Islamic religious education, because the purpose of value education is to educate human behavior in the teachings of Islam better known by educating noble morals based on Al-Quran and Hadith. Through value education, the objectives, materials, methods, evaluation activities, and educators in Islamic religious education should support the achievement of the value of education goals. Implementation of values education in Islamic religious education can help learners become human beings who understand the values of their religious teachings and apply these values in their daily lives, so that any negative effects of changing times can be anticipated learners better.